Fungal infections in burns: Diagnosis and management - Capoor, Malini R.; Sarabahi, Sujata; Tiwari, Vinay Kumar; Narayanan, Ravi Prakash (Indian Journal of Plastic Surgery, 2010)
Burn wound infection (BWI) is a major public health problem and the most devastating form of trauma worldwide. Fungi cause BWI as part of monomicrobial or polymicrobial infection, fungaemia, rare aggressive soft tissue infection and as opportunistic infections. The risk factors for acquiring fungal infection in burns include age of burns, total burn size, body surface area (BSA) (30–60%), full thickness burns, inhalational injury, prolonged hospital stay, late surgical excision, open dressing, artificial dermis, central venous catheters, antibiotics, steroid treatment, long-term artificial ventilation, fungal wound colonisation (FWC), hyperglycaemic episodes and other immunosuppressive disorders. Most of the fungal infections are missed owing to lack of clinical awareness and similar presentation as bacterial infection coupled with paucity of mycology laboratories. Expedient diagnosis and treatment of these mycoses can be life-saving as the mortality is otherwise very high. Emergence of resistance in non-albicans Candida spp., unusual yeasts and moulds in fungal BWI, leaves very few fungi susceptible to antifungal drugs, leaving many patients susceptible. There is a need to speciate fungi as far as the topical and systemic antifungal is concerned. Deep tissue biopsy and other relevant samples are processed by standard mycological procedures using direct microscopy, culture and histopathological examination. Patients with FWC should be treated by aggressive surgical debridement and, in the case of fungal wound infection (FWI), in addition to surgical debridement, an intravenous antifungal drug, most commonly amphotericin B or caspofungin, is prescribed followed by de-escalating with voriconazole or itraconazole, or fluconazole depending upon the species or antifungal susceptibility, if available. The propensity for fungal infection increases, the longer the wound is present. Therefore, the development of products to close the wound more rapidly, improvement in topical antifungal therapy with mould activity and implementation of appropriate systemic antifungal therapy guided by antifungal susceptibility may improve the outcome for severely injured burn victims.
Keywords: Burns; fungal infections; moulds; yeasts